PENGELOLAAN TENAGA PENDIDIK DI SATUAN KELOMPOK BERMAIN (KB) - Regina, Putri; Fahmi, Fahmi; Wulandari, Retno (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
Educators in PAUD must at least have D3 Early Childhood Education or S1 non-formal education, but there are still many educators in PAUD who only have high school education or equivalent. The management of teaching staff in play group units (KB), where most of the facts that occur in the field in play group units do not meet the quality of competence for early childhood education teachers, because until now most teachers in these institutions still have not got a bachelor's degree or only graduated from high school or the equivalent. can affect teacher competence, especially in pedagogical and professional competencies so that the results obtained and achieved are not maximized in playgroup units. The purpose of this article is to describe and identify various aspects regarding the management of teaching staff in playgroup units so that later it is expected to be able to improve the quality and quality of teaching staff in various playgroup institutional units so that the desired goals can be achieved, because if the quality of teaching staff is fulfilled then will have a very good impact on students and can achieve goals in the play group institutional unit. The method used in this research is literature review, in which researchers collect various data from various sources to be used as material for making articles about the management of educators in playgroup units (KB).